Galloping instability and control of a rigid pendulum in a flowing soap film. (July 2015) - Orchini, Alessandro; Kellay, Hamid; Mazzino, Andrea
Abstract: A pendulum suspended in a fast flowing soap film may show sustained oscillations. The conditions necessary for self-excited motion to occur are outlined: a flow velocity above a threshold value along with geometrical constraints. The role of vortex shedding is discussed, and the observed instability is shown to be well-described by the galloping instability. Experimental results are supported by numerical simulations. Furthermore, we observe that the instability may be suppressed by attaching a long enough filament to the rear of the pendulum. Abstract : Highlights: We investigate the dynamics of a rigid pendulum oscillating in a flowing soap film. An instability is found for some set of flow and geometrical parameters. We identify the instability as galloping using a classical analytical model. Results are verified by means of finite difference CFD simulations. We identify a mechanism that inhibits galloping by transferring energy to an elastic filament.